Did Covid-19 Precautions and Lockdowns Cause Better Air Quality? Empirical Findings from Turkish Provinces - ARI, ALİ (My University, 2022)
The Covid-19 pandemic have dramatically affected the socio-economic structure in the world since governments put into action considerable precautions including lockdowns to reduce the speed of the contagion. Focusing on this point, we empirically investigate the environmental outcomes of the Covid-19 precautions and lockdowns in Turkey. The empirical analysis through the data obtained from different measurement stations indicate that the air pollution in the selected Turkish cities decreased due to the implemented precautions. The findings suggest that the Covid-19 might be an opportunity to rethink some economic and behavioral practices, as demonstrated by the reduction in the emission of air pollutants.
Keywords: Sosyal ve Beşeri Bilimler; İktisat; Social Sciences and Humanities; Economics; EKONOMİ; Ekonomi ve İş; Sosyal Bilimler (SOC); ECONOMICS; ECONOMICS & BUSINESS; Social Sciences (SOC); Economics and Econometrics; Economics, Econometrics and Finance (miscellaneous); General Economics, Econometrics and Finance; Social Sciences & Humanities; Covid-19 pandemic; social interaction; greenhouse gas emission